2016
DOI: 10.1111/ijn.12451
|View full text |Cite
|
Sign up to set email alerts
|

Sleep problems, anxıety, depressıon and fatıgue on famıly members of adult intensıve care unıt patıents

Abstract: The purpose of this study was to determine the levels of sleep problems, anxiety, depression and fatigue in family members of intensive care patients in Turkey and factors affecting these complaints. This cross-sectional study was carried out with 350 first-degree relatives of intensive care patients at a university and state hospital. Data were collected between 5 January and 30 May 2014 using a personal information form, the Visual Analogue Scale for Fatigue, the Hospital Anxiety and Depression Scale and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…Noteworthy, anxiety is the commonest psychological disorder in the PICS-F cluster experienced by family members. Anxiety has been reported among 81.4% of family members, while depression is experienced in up to 94.2% of family members of ICU patients [11]. A similar study of Kose et al [12] showed that 35.9% and 71.8% of family members experienced anxiety and depression respectively.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Noteworthy, anxiety is the commonest psychological disorder in the PICS-F cluster experienced by family members. Anxiety has been reported among 81.4% of family members, while depression is experienced in up to 94.2% of family members of ICU patients [11]. A similar study of Kose et al [12] showed that 35.9% and 71.8% of family members experienced anxiety and depression respectively.…”
Section: Discussionmentioning
confidence: 88%
“…These have been largely studied depending on the component of PICS-F under consideration. Celik et al [11] showed that married, low income and family members who used regular medication experienced significantly higher scores of anxiety and depression. A positive association was also liked to age, and length of hospital stay.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Previous studies have found that when pleasantness was perceived as high, the environment was also perceived as safe, secure, and stimulating (Bengtsson & Carlsson, 2006;Shih & Ramilo, 2014). Previous research has reported that families of critically ill patients cared for in ICUs experience serious types of ill-being such as depression, anxiety, and fatigue (Apple, 2014;Celik et al, 2016;Day et al, 2013); sometimes, they even develop post-traumatic stress disorder (Petrinec & Daly, 2016;Stayt & Venes, 2019;Wintermann et al, 2016). These findings from the refurbished intervention room can be a way of reducing some elements of ill-being.…”
Section: Discussionmentioning
confidence: 99%
“…The alien environment, with its advanced monitoring and aggressive treatments of critically ill patients, is harsh for the family members (Imanipour et al, 2019;Ruckholdt et al, 2019;Turner-Cobb et al, 2016). Experiences like anxiety, sadness, depression, and fatigue in family members of ICU patients have been reported repeatedly in prior studies (Apple, 2014;Celik et al, 2016;Day et al, 2013). These stressful experiences can sometimes develop into more persistent conditions such as post-traumatic stress disorder (Petrinec & Daly, 2016).…”
Section: Visiting the Intensive Care Unit (Icu)mentioning
confidence: 99%
“…Celik et al. showed that out of 350 family members studied, 76% experienced moderate to severe problems, of these 81.4% experienced anxiety, and 94.2% experienced depression and an average score of fatigue of 79.4. In addition, Kose's et al.…”
Section: Introductionmentioning
confidence: 99%